D4N2024 Presentation Showcase – THEMATIC SESSION 6b: Digital innovations across food and health systems - Ray, Manojit; Vadsaria, Khadija; Ali, Asif; Khan, Umber; Karunarathna, Nilmini; Mandal, Raj Nandan; Mendhe, Roshan; Nordhagen, Stella (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – THEMATIC SESSION 6b: Digital innovations across food and health systems